Prognostic Significance of the Sodium Channel Blocker Test in Patients With Brugada Syndrome - Ueoka, Akira (J Am Heart Assoc, 2018)
BACKGROUND: A drug provocation test using a sodium channel blocker (SCB) can unmask a type 1 ECG pattern in patients with Brugada syndrome. However, the prognostic value of the results of an SCB challenge is limited in patients with non–type 1 ECG. We investigated the associations of future risk for ventricular fibrillation with SCB‐induced ECG changes and ventricular tachyarrhythmias (VTAs). METHODS AND RESULTS: We administered intravenous pilsicainide to 245 consecutive patients with Brugada syndrome (181 patients with spontaneous type 1 ECG, 64 patients with non–type 1 ECG). ECG parameters before and after the test and occurrence of drug‐induced VTAs were evaluated. During a mean follow‐up period of 113±57 months, fatal VTA events occurred in 31 patients (sudden death: n=3, ventricular tachycardia/ventricular fibrillation: n=28). Symptomatic patients and spontaneous type 1 ECG were associated with future fatal arrhythmic events. Univariable analysis of ECG parameters after the test showed that long PQ and QRS intervals, high ST level, and SCB‐induced VTAs were associated with later VTA events during follow‐up. Multivariable analysis showed that symptomatic patients, high ST level (V1) ≥0.3 mV after the test, and SCB‐induced VTAs were independent predictors for future fatal arrhythmic events (hazard ratios: 3.28, 2.80, and 3.62, 95% confidence intervals: 1.54–7.47, 1.32–6.35, and 1.64–7.75, respectively; P<0.05). CONCLUSIONS: SCB‐induced VTAs and ST‐segment augmentation are associated with an increased risk of the development of ventricular tachycardia/ventricular fibrillation events during follow‐up in patients with Brugada syndrome.